APPROACHES TO THE DIAGNOSIS AND MANAGEMENT OF UROLITHIASIS: A LITERATURE REVIEW - Supandi Syahputra; Khuzaini (PT. Radja Intercontinental Publishing, 2025)
Urolithiasis is one of the most common urological conditions encountered in clinical practice and continues to show a rising global trend. The wide variation in clinical presentation, along with rapid advances in diagnostic and therapeutic technologies, necessitates a comprehensive understanding of its management approaches. This literature review aims to summarize recent developments in the diagnosis and management of urolithiasis and to compare the effectiveness of various interventional modalities. A narrative literature review was conducted using articles published between 2022 and 2025, identified through PubMed and Google Scholar. Keywords included urolithiasis, diagnosis, management, ESWL, URS, and PCNL. Relevant articles were selected based on topical relevance, publication quality, and availability of clinically meaningful data. Non-contrast CT scan remains the most accurate diagnostic modality for detecting urinary stones, whereas ultrasonography remains valuable in specific populations and resource-limited settings. In terms of treatment, ESWL is effective for small to medium-sized stones with low density, URS demonstrates higher success rates for ureteral stones, and PCNL remains the primary option for large or complex stones. Recurrence prevention through metabolic evaluation, dietary modification, and pharmacologic therapy significantly reduces the risk of stone formation. Diagnostic and therapeutic strategies for urolithiasis have advanced considerably; However, optimal modality selection must be tailored to individual patient and stone characteristics. Personalized approaches and sustained preventive strategies are essential to improving clinical outcomes and reducing recurrence rates.